Preparation method of biocarbon-molybdenum sulfide-tungsten sulfide composite and composite

By symbiotically growing tungsten sulfide and molybdenum sulfide on the surface of the carbon source to form an overlapping structure, the shortcomings of existing electrode materials in terms of conductivity, rate performance and cycle stability are solved, and efficient potassium ion diffusion and potassium storage capacity are achieved, improving the overall performance of the electrode materials.

CN115763757BActive Publication Date: 2025-04-18BEIHANG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211526630.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-30
Publication Date
2025-04-18
Estimated Expiration
2042-11-30

AI Technical Summary

Technical Problem

The existing transition metal sulfide electrode materials still need to be improved in terms of conductivity, rate performance and charge and discharge cycle stability, and the tungsten sulfide generation conditions during the hydrothermal preparation process are harsh, the synthesis efficiency is low, making it difficult to achieve large-scale application.

Method used

The preparation method of symbiotically growing two-dimensional layered tungsten sulfide and molybdenum sulfide on the surface of the carbon source is adopted. The nucleation is provided through molybdenum sulfide, which reduces the difficulty of growth and improves the preparation efficiency. The overlapping structure is formed by symbiotic growth of tungsten sulfide and molybdenum sulfide, expands the layer spacing of lithium ion and potassium ion intercalation, and improves the potassium ion diffusion efficiency and potassium storage capacity performance of electrode materials.

Benefits of technology

It improves the potassium ion diffusion efficiency and potassium storage capacity performance of the electrode material, reduces the volume expansion during the charging and discharging process, improves the cyclic stability of the electrode material, and achieves high-speed performance and structural stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115763757B_ABST
    Figure CN115763757B_ABST
Patent Text Reader

Abstract

The present invention relates to a preparation method of a biocarbon-molybdenum sulfide-tungsten sulfide composite, a biocarbon-molybdenum sulfide-tungsten sulfide composite, a negative electrode for a potassium ion battery, a potassium ion battery, and the use of the above-mentioned preparation method in preparing a negative electrode for a potassium ion battery. The preparation method of the above-mentioned biocarbon-molybdenum sulfide-tungsten sulfide composite comprises the following steps: a reaction solution preparation step: dissolving sodium tungstate, hydroxylamine hydrochloride, thiourea and sodium molybdate in deionized water, stirring evenly, and preparing a reaction solution; a hydrothermal reaction step: mixing the reaction solution with biocarbon in a reactor and then performing a hydrothermal reaction at a constant temperature; a filtering and drying step: after the hydrothermal reaction step is completed, filtering, washing, and drying are performed to obtain a composite precursor; a calcining step: calcining the composite precursor under an inert gas atmosphere to obtain a biocarbon-molybdenum sulfide-tungsten sulfide composite, and the calcination temperature is 850-950°C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of batteries, and in particular to a biocarbon-molybdenum sulfide-tungsten sulfide composite electrode material and a preparation method thereof. Background Art

[0002] As negative electrode materials for lithium-ion batteries, potassium-ion batteries, etc., transition metal sulfides have better conductivity and good diffusion kinetics for lithium ions, potassium ions, etc. due to their weaker bond energy than transition metal oxides. In addition, they also have higher theoretical capacity. In addition, due to the low barrier to ion migration and embedding reactions, the interlayer spacing of layered transition metal sulfides facilitates the rapid diffusion, embedding and de-embedding of lithium ions, potassium ions, etc., and therefore have great potential in the fields of lithium storage and potassium storage.

[0003] In the prior art, in order to improve the conductivity of transition metal sulfides, Patent Document 1 discloses a composite material with carbon microspheres as a supporting skeleton and transition metal sulfides embedded on its surface. However, the obtained composite material still needs to be improved in terms of conductivity, rate performance, charge and discharge cycle, etc.

[0004] In addition, for the preparation of transition metal sulfides, there are methods such as hydrothermal synthesis and chemical vapor deposition. However, these preparation methods still have the problems of low efficiency and the performance of the obtained composite materials needs to be improved.

[0005] Patent document 1: CN110690419A Summary of the invention

[0006] After in-depth research, the inventors found that due to the high migration efficiency of tungsten, tungsten sulfide is used as a transition metal sulfide in the negative electrode material of lithium-ion batteries, potassium-ion batteries, etc., which is conducive to the diffusion of lithium ions, potassium ions, etc. However, in the existing hydrothermal preparation process, the generation conditions of tungsten sulfide are harsh and the synthesis efficiency is low, making it difficult to achieve large-scale application. The inventors of the present invention have innovatively adopted a preparation method of in-situ co-growth of two-dimensional layered tungsten sulfide and molybdenum sulfide on the surface of a carbon source. By using molybdenum sulfide for co-growth, a large number of nuclei are provided for tungsten sulfide, which reduces the growth difficulty of tungsten sulfide and improves the preparation efficiency. In addition, by co-growth of tungsten sulfide and molybdenum sulfide to form an overlapping structure of tungsten sulfide layer and molybdenum sulfide layer, the interlayer spacing of lithium ions, potassium ions, etc. embedded layers is expanded, the potassium ion diffusion efficiency of the electrode material and the potassium storage capacity performance of the electrode material are improved, while the volume expansion during the charge and discharge process is reduced, and the cycle stability of the electrode material is improved. Furthermore, by selecting biochar as the carbon source, the structural stability and electrochemical activity during the insertion (deinsertion) of lithium ions, potassium ions, etc. are improved, which is conducive to achieving high-rate performance and cycle stability.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] In one aspect, the present invention provides a method for preparing a biocarbon-molybdenum sulfide-tungsten sulfide composite, comprising:

[0009] Reaction solution preparation steps: dissolving sodium tungstate, hydroxylamine hydrochloride, thiourea and sodium molybdate in deionized water, stirring evenly, to prepare a reaction solution;

[0010] Hydrothermal reaction step: mixing the reaction solution with biochar in a reactor to cause a hydrothermal reaction at a constant temperature;

[0011] Filtration and drying step: After the hydrothermal reaction step is completed, filtering, washing and drying are performed to obtain a composite precursor;

[0012] Calcination step: calcining the composite precursor in an inert gas atmosphere to obtain a biocarbon-molybdenum sulfide-tungsten sulfide composite, the calcination temperature being 850-950°C.

[0013] On the other hand, the present invention also provides a biocarbon-molybdenum sulfide-tungsten sulfide composite, which is prepared by the aforementioned preparation method of the biocarbon-molybdenum sulfide-tungsten sulfide composite.

[0014] On the other hand, the present invention also provides a negative electrode for a potassium ion battery, which comprises the aforementioned biocarbon-molybdenum sulfide-tungsten sulfide composite.

[0015] In another aspect, the present invention provides a potassium ion battery, comprising the aforementioned negative electrode for a potassium ion battery.

[0016] On the other hand, the present invention provides a composite prepared by the aforementioned method for preparing a biocarbon-molybdenum sulfide-tungsten sulfide composite or use of the aforementioned composite in preparing a negative electrode for a potassium ion battery.

[0017] The preparation method of the biocarbon-molybdenum sulfide-tungsten sulfide composite of the present invention uses molybdenum sulfide for co-growth, which provides a large number of nuclei for tungsten sulfide, reduces the growth difficulty of tungsten sulfide, and improves the preparation efficiency. In addition, an overlapping structure of a tungsten sulfide layer and a molybdenum sulfide layer is formed by the co-growth of tungsten sulfide and molybdenum sulfide, which expands the interlayer spacing of embedded layers such as lithium ions and potassium ions, improves the potassium ion diffusion efficiency of the electrode material and the potassium storage capacity performance of the electrode material, and at the same time reduces the volume expansion during the charge and discharge process, and improves the cycle stability of the electrode material.

[0018] Furthermore, in the biochar-molybdenum sulfide-tungsten sulfide composite of the present invention, by using biochar as a carbon source, the structural stability and electrochemical activity during the embedding (de-embedding) of lithium ions, potassium ions, etc. are improved, thereby achieving improvements in rate performance and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1is a scanning electron microscope image of the composite prepared in Example 1 of the present invention;

[0020] Figure 2 is a magnified scanning electron microscope image of the composite prepared in Example 1 of the present invention;

[0021] Figure 3 is a scanning electron microscope image of the composite prepared in Comparative Example 1 of the present invention;

[0022] Figure 4 The specific capacity and coulombic efficiency values ​​of the electrode prepared by the biocarbon-molybdenum sulfide-tungsten sulfide composite obtained in Example 1 were measured at different current densities;

[0023] Figure 5 It is a single cycle specific capacity-voltage diagram of the electrode prepared using the composite obtained in Comparative Example 1 and Example 1. DETAILED DESCRIPTION

[0024] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. In the examples, those without specifying specific techniques or conditions are carried out according to the techniques or conditions described in the literature in this area or according to the product specification. Those without specifying the manufacturer of reagents or instruments used are all conventional products that can be obtained commercially. In the following examples, if not clearly stated, "%" refers to weight percentage.

[0025] The term "constant temperature" in the present invention refers to a temperature that differs from a specific temperature by no more than 0.5°C. For example, to carry out a reaction at a constant temperature of 180°C means to carry out the reaction within a temperature range of 179.5°C to 180.5°C, that is, the temperature during the reaction differs from the specific temperature of 180°C by 0.5°C.

[0026] A method for preparing a biocarbon-molybdenum sulfide-tungsten sulfide composite according to one embodiment includes the following steps:

[0027] Reaction solution preparation steps: dissolving sodium tungstate, hydroxylamine hydrochloride, thiourea and sodium molybdate in deionized water, stirring evenly, to prepare a reaction solution;

[0028] Hydrothermal reaction step: mixing the reaction solution with biochar in a reactor to cause a hydrothermal reaction at a constant temperature;

[0029] Filtration and drying step: After the hydrothermal reaction step is completed, filtering, washing and drying are performed to obtain a composite precursor;

[0030] Calcination step: calcining the composite precursor in an inert gas atmosphere to obtain a biocarbon-molybdenum sulfide-tungsten sulfide composite, the calcination temperature being 850-950°C.

[0031] In the preparation method of the biochar-molybdenum sulfide-tungsten sulfide composite of the present invention, molybdenum sulfide is used as the nucleation active point of tungsten sulfide, thereby solving the problem of difficulty in nucleation of tungsten sulfide. In the composite prepared thereby, the biochar having a honeycomb three-dimensional structure plays the role of a reinforcing body to make the composite structure stable, and the tungsten sulfide and molybdenum sulfide nanosheets are evenly anchored on the surface of the biochar, thereby having good capacitance performance and charge transfer performance, and can be used as an electrode material for lithium ion batteries and potassium ion batteries with high capacity, high rate performance and long cycle life. In addition, by using biochar as a carbon source, the structural stability and electrochemical activity during the embedding (de-embedding) of lithium ions, potassium ions, etc. are improved, which is conducive to achieving high rate performance and cycle stability.

[0032] Below, each step of the above-mentioned preparation method is described in detail.

[0033] [Reaction solution preparation step]

[0034] In the above reaction solution preparation step, sodium tungstate, hydroxylamine hydrochloride, thiourea and sodium molybdate are dissolved in deionized water and stirred evenly to obtain a light yellow transparent reaction solution. The reaction solution prepared in the above reaction solution preparation step is used as the reaction solution for subsequently generating tungsten sulfide on the surface of biochar using molybdenum sulfide as a nucleation active point.

[0035] In some embodiments, in the obtained reaction solution, for example, the concentration of hydroxylamine hydrochloride is, for example, 0.1 to 0.6 mol / L, and the concentration of thiourea is, for example, 0.1 to 0.9 mol / L. From the perspective of ensuring sufficient sulfur source, the molar ratio of hydroxylamine hydrochloride to thiourea can be, for example, in the range of 1:1 to 1.5.

[0036] In some embodiments, the concentration of sodium tungstate is, for example, 0.05 to 0.2 mol / L, and the concentration of sodium molybdate is, for example, 0.0005 to 0.1 mol / L. Thus, the promoting effect of sodium molybdate on the growth of tungsten sulfide is ensured, and the concentration of sodium molybdate does not exceed that of sodium tungstate, so that it will not squeeze the sulfur source with sodium molybdate, curb the formation of tungsten sulfide, and prevent excessive concentrations of sodium tungstate and sodium molybdate from causing excessive nitrogen to be generated during the reaction and causing excessive pressure in the reactor.

[0037] [Hydrothermal reaction steps]

[0038] In the hydrothermal reaction step, the biochar is mixed with the reaction solution prepared in the reaction solution preparation step in a reactor and reacted at a constant temperature.

[0039] The aforementioned "constant temperature" may be, for example, a temperature in the range of 180 to 240°C, that is, the reaction temperature may be constant at a specific temperature of 180 to 240°C. For example, it may be a specific temperature selected from 180 to 240°C, such as 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, etc. For example, in the case of a constant temperature of 190°C, the temperature fluctuation of the reaction system is controlled within the range of ±0.5°C, that is, the reaction temperature is 189.5°C to 190.5°C.

[0040] The reaction time may be, for example, 8 to 48 hours, and the reaction time may be appropriately adjusted according to the reaction temperature.

[0041] The aforementioned "biochar" refers to a porous carbon processed from biological organic matter, such as animal tissue, plant tissue, etc. Examples of the aforementioned biochar include charcoal, carbonized products of organic waste, carbonized products of animal and plant tissues, and carbonized products of biological feces. The density of the aforementioned biochar is preferably 0.05 to 0.15 g / cm 3 By setting the density of biochar to 0.05-0.15 g / cm 3 The biochar can be obtained, for example, by calcining natural wood. The calcination temperature can be, for example, 850 to 950° C. The natural wood is preferably balsa wood.

[0042] In some embodiments, the reaction is preferably carried out under the condition that the biochar is immersed in the reaction solution and the pressure is maintained at 0.015-0.020 MPa, thereby accelerating the process of the reaction solution infiltrating the charcoal and improving the reaction efficiency.

[0043] The reaction occurring in the aforementioned hydrothermal reaction step is as follows:

[0044] CH4N2S+2H2O══CO2+2NH3+H2S

[0045] Na2WO4+4H2S══Na2WS4+4H2O

[0046] Na2MoO4+4H2S══Na2MoS4+4H2O

[0047] Na2WS4+2NH2OH·HCl══WS2+N2+2H2S+2H2O+2NaCl

[0048] Na2MoS4+2NH2OH·HCl══MoS2+N2+2H2S+2H2O+2NaCl

[0049] By adjusting the hydrothermal reaction time, tungsten sulfide two-dimensional nanosheets with a size of 100 to 300 nm are generated, which is beneficial to the transmission of lithium ions, potassium ions, etc.

[0050] [Filtration steps]

[0051] In the filtration step, the reaction solution after the hydrothermal reaction step is filtered, washed and dried to obtain the composite precursor. The filtration can be carried out by normal pressure filtration, reduced pressure filtration, hot filtration and other filtration methods, without particular limitation.

[0052] As the cleaning liquid for the above cleaning, deionized water, ethanol, etc. can be used. The cleaning can be performed once or repeatedly, for example, 2 to 5 times. The above drying can be performed by normal pressure drying, reduced pressure drying, etc., and the drying temperature can be, for example, in the range of 30 to 80°C.

[0053] [Calcination step]

[0054] In the calcination step, the composite precursor is calcined in an inert gas atmosphere to obtain a biocarbon-molybdenum sulfide-tungsten sulfide composite, and the calcination temperature is, for example, 850-950° C. The inert gas atmosphere is, for example, nitrogen or argon atmosphere.

[0055] [Other steps]

[0056] In some embodiments, the aforementioned method for preparing the biocarbon-molybdenum sulfide-tungsten sulfide composite optionally further comprises the following steps:

[0057] Repeating the reaction step: reacting the complex precursor obtained in the filtering step with the new reaction solution prepared in the reaction solution preparing step, followed by washing and drying.

[0058] By repeating the above reaction steps, the dried biochar composite reacts with the new reaction solution prepared in the reaction solution preparation step, thereby increasing the loading amount of the biochar surface active substance. The higher the content of tungsten sulfide in the composite, the higher the potassium storage capacity.

[0059] As the cleaning liquid for the above cleaning, deionized water, ethanol, etc. can be used. The cleaning can be performed once or repeatedly for multiple times, for example, 1 to 5 times, preferably 2 to 5 times.

[0060] The drying may be performed by normal pressure drying, reduced pressure drying or the like, and the drying temperature may be, for example, in the range of 30 to 80°C.

[0061] [Biocarbon-Molybdenum Sulfide-Tungsten Sulfide Composite]

[0062] The biochar-molybdenum sulfide-tungsten sulfide composite is prepared by the aforementioned method for preparing the biochar-molybdenum sulfide-tungsten sulfide composite. In the biochar-molybdenum sulfide-tungsten sulfide composite obtained,

[0063] In some embodiments of the aforementioned biochar-molybdenum sulfide-tungsten sulfide composite, tungsten sulfide is a nanosheet with a size of 100 to 300 nm, molybdenum sulfide is a nanosheet with a size of 100 to 300 nm, and tungsten sulfide and molybdenum sulfide are embedded in the surface of the biochar.

[0064] In some embodiments of the aforementioned biochar-molybdenum sulfide-tungsten sulfide composite, the mass percentage of tungsten sulfide is, for example, 10-80% and the mass percentage of molybdenum sulfide is, for example, 0.2-0.5% relative to the entire composite. The higher the content of tungsten sulfide in the composite, the higher the potassium storage capacity.

[0065] The aforementioned "biochar" refers to a porous carbon processed from biological organic matter, such as animal tissue, plant tissue, etc. Examples of the aforementioned biochar include charcoal, carbonized products of organic waste, carbonized products of animal and plant tissues, and carbonized products of biological feces. The density of the aforementioned biochar is preferably 0.05 to 0.15 g / cm 3 By setting the density of biochar to 0.05-0.15 g / cm 3 The range of porosity is high and the specific surface area is large, which is conducive to ion transport. Low-density balsa wood is selected as the carbonization raw material, and the density of its carbonized product is about 0.05-0.15g / cm 3 .

[0066] [Anode for Potassium Ion Batteries]

[0067] The negative electrode for potassium ion battery contains the aforementioned biochar-molybdenum sulfide-tungsten sulfide composite. Thus, by using biochar as a carbon source, the structure of the composite contained in the negative electrode is stable, so that it has good capacitance performance and charge transfer performance, and can be used as an electrode material for potassium ion battery with high capacity, high rate performance and long cycle life.

[0068] [Potassium ion battery]

[0069] The potassium ion battery contains the aforementioned negative electrode for potassium ion batteries. Since the structure of the composite contained in the negative electrode is stable, the tungsten sulfide and molybdenum sulfide nanosheets are evenly anchored on the surface of the biochar, thus having good capacitance performance and charge transfer performance, and can be used as an electrode material for potassium ion batteries with high capacity, high rate performance and long cycle life.

[0070] [use]

[0071] Correspondingly, the composite prepared by the aforementioned method for preparing the biocarbon-molybdenum sulfide-tungsten sulfide composite for the negative electrode of the potassium ion battery or the use of the aforementioned composite in preparing the negative electrode for the potassium ion battery.

[0072] Example

[0073] Example 1

[0074] The original wood was cut into small pieces of 10mm×10mm×5mm in size, calcined at 850℃ for 2 hours in a nitrogen atmosphere, then washed with deionized water and dried at 80℃ for 10 hours to obtain biochar. 0.05mol / L sodium tungstate, 0.1mol / L hydroxylamine hydrochloride, 0.15mol / L thiourea and 0.0005mol / mL sodium molybdate were dissolved in 30℃ deionized water, and magnetically stirred for 30 minutes to obtain a light yellow transparent solution. The biochar and the above light yellow transparent solution were moved into a reactor together and reacted at a constant temperature of 200℃ for 24 hours. After the reaction was completed, the reaction solution was filtered to obtain the biochar composite 1. The biochar composite 1 was washed with deionized water and anhydrous ethanol alternately twice, dried for 10 hours, and then the reaction was repeated 3 times with a new reaction solution. The filtered product was washed with deionized water and anhydrous ethanol alternately twice, dried at 80°C for 10 hours, and then calcined at 850°C for 2 hours in a nitrogen atmosphere to obtain the biochar-molybdenum sulfide-tungsten sulfide composite 1. The scanning electron microscope photo of the biochar-molybdenum sulfide-tungsten sulfide composite 1 is shown in FIG. Figure 1 , Figure 2 As shown. Figure 1 , Figure 2 It can be seen that tungsten sulfide and molybdenum sulfide nanosheets grow evenly on the surface of biochar.

[0075] The prepared biocarbon-molybdenum sulfide-tungsten sulfide composite 1, conductive carbon black and polyvinylidene fluoride were mixed in a mass ratio of 8:1:1, wherein 1 mass part of polyvinylidene fluoride was first dissolved in 19 mass parts of methyl pyrrolidone, and then 8 mass parts of biocarbon-molybdenum sulfide-tungsten sulfide composite 1 and 1 mass part of conductive carbon black were dispersed therein, and stirred for 3 hours to obtain a uniformly mixed slurry. The prepared slurry was applied to aluminum foil with a thickness of about 20 μm, and then dried at 110°C for 24 hours to prepare a biocarbon-molybdenum sulfide-tungsten sulfide electrode sheet 1. The electrolyte solution was a 0.8 mol / L potassium hexafluorophosphate solution, and the solvent was ethylene carbonate: diethyl carbonate in a volume ratio of 1:1.

[0076] Example 2

[0077] The concentration of sodium molybdate in Example 1 was adjusted to 0.001 mol / mL to obtain the biochar-molybdenum sulfide-tungsten sulfide composite 2. The weight gain of the biochar before and after the reaction was 19%.

[0078] Example 3

[0079] The concentration of sodium molybdate in Example 1 was adjusted to 0.005 mol / mL to obtain the biochar-molybdenum sulfide-tungsten sulfide composite 3. The weight gain of the biochar before and after the reaction was 28%.

[0080] Example 4

[0081] The concentration of sodium molybdate in Example 1 was adjusted to 0.01 mol / mL to obtain a biochar-molybdenum sulfide-tungsten sulfide composite 4. The weight gain of the biochar before and after the reaction was 32%.

[0082] Example 5

[0083] The concentration of sodium tungstate in Example 1 was adjusted to 0.1 mol / mL to obtain the biochar-molybdenum sulfide-tungsten sulfide composite 6. The weight gain of the biochar before and after the reaction was 18%.

[0084] Example 6

[0085] The concentration of sodium tungstate in Example 1 was adjusted to 0.2 mol / mL to obtain the biochar-molybdenum sulfide-tungsten sulfide composite 7. The weight gain of the biochar before and after the reaction was 19%.

[0086] Comparative Example 1

[0087] Comparative Example 1 was prepared with reference to Example 1, except that sodium molybdate was not added, so as to obtain a biocarbon-tungsten sulfide composite 2. A pole piece 2 was prepared with reference to Example 1.

[0088] The scanning electron microscope image of the obtained biocarbon-tungsten sulfide composite 2 is shown in Figure 3 .from Figure 3 It can be seen that without using sodium molybdate, the tungsten sulfide in the composite 2 is irregular granular, the agglomerate structure is uneven in size and distribution, and the tungsten sulfide does not completely cover the surface of the biochar, and a large amount of the biochar surface is exposed. In contrast, in Example 1, the sodium molybdate contained in the reaction raw material will be quickly and evenly reduced to molybdenum sulfide on the surface of the charcoal. Therefore, Figure 1 , Figure 2 As shown, there is no exposed carbon in the composite 1 of Example 1 to which sodium molybdate is added, and the nucleation of molybdenum sulfide also promotes the growth of tungsten sulfide, so tungsten sulfide also grows uniformly on the surface of charcoal.

[0089] [Experimental measurement of specific capacity and coulombic efficiency]

[0090] The potassium metal half-cell test was performed on the electrode 1 and the electrode 2 using a LANHE CT3002A battery tester to test the charge and discharge performance of the electrode at current densities of 10 mA / g, 20 mA / g, 50 mA / g, 100 mA / g, 200 mA / g, and 500 mA / g from a voltage range of 0.1 to 2.5 V. The measured results are shown in Figure 4 .from Figure 4It can be seen that the reversible capacity of electrode 1 is 285 mAh / g, 253 mAh / g, 216 mAh / g, 174 mAh / g, 130 mAh / g and 80 mAh / g at current densities of 10 mA / g, 20 mA / g, 50 mA / g, 100 mA / g, 200 mA / g and 500 mA / g respectively.

[0091] [Single cycle specific capacity-voltage measurement]

[0092] The potassium metal half-cell test was performed on the electrode pieces 1 and 2 using a LANHE CT3002A battery tester to test the single cycle specific capacity-voltage diagram of the electrode in the voltage range of 0.1 to 2.5 V at a current density of 10 mA / g. Figure 5 As shown. Figure 5 It can be seen that the specific capacity performance of the electrode piece 1 of Example 1 is significantly higher than that of the electrode piece 2 of Comparative Example 1. Compared with the sample of Comparative Example 1, the sample of Example 1 has obvious voltage platforms at 0.9-1.0V and 1.2-1.3V.

[0093] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0094] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0095] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for preparing a biocarbon-molybdenum sulfide-tungsten sulfide composite, comprising the following steps: Reaction solution preparation steps: dissolving sodium tungstate, hydroxylamine hydrochloride, thiourea and sodium molybdate in deionized water, stirring evenly, to prepare a reaction solution; Hydrothermal reaction step: mixing the reaction solution with biochar in a reactor to cause a hydrothermal reaction at a constant temperature; Filtration and drying step: After the hydrothermal reaction step is completed, filtering, washing and drying are performed to obtain a composite precursor; Calcination step: calcining the composite precursor in an inert gas atmosphere to obtain a biocarbon-molybdenum sulfide-tungsten sulfide composite, the calcination temperature is 850-950°C, Wherein, in the reaction solution, the concentration of sodium tungstate is 0.05-0.2 mol / L, the concentration of sodium molybdate is 0.0005-0.1 mol / L, the concentration of hydroxylamine hydrochloride is 0.1-0.6 mol / L, and the concentration of thiourea is 0.1-0.9 mol / L. In the hydrothermal reaction step, the biochar is immersed in the reaction solution and the reaction is carried out at a pressure of 0.015 to 0.020 MPa, and the reaction temperature is a constant temperature in the range of 180 to 240°C.

2. The method for preparing the biocarbon-molybdenum sulfide-tungsten sulfide composite according to claim 1, further comprising the following steps: Repeating the reaction step: reacting the composite precursor with the new reaction solution prepared in the reaction solution preparation step, followed by washing and drying; The repeated reaction step is performed 1 to 5 times.

3. A biocarbon-molybdenum sulfide-tungsten sulfide composite, which is prepared by the preparation method of the biocarbon-molybdenum sulfide-tungsten sulfide composite according to claim 1 or 2.

4. The biocarbon-molybdenum sulfide-tungsten sulfide composite according to claim 3, wherein: The tungsten sulfide is a nanosheet with a size of 100 to 300 nm, and the molybdenum sulfide is a nanosheet with a size of 100 to 300 nm. The tungsten sulfide and the molybdenum sulfide are embedded on the surface of the biochar. Relative to the entire composite, the mass percentage of the tungsten sulfide is 10-80%, and the mass percentage of the molybdenum sulfide is 0.2-0.5%.

5. The biocarbon-molybdenum sulfide-tungsten sulfide composite according to claim 3, wherein: The density of the biochar is 0.05-0.15 g / cm 3 . 6 . A negative electrode for a potassium ion battery, comprising the biocarbon-molybdenum sulfide-tungsten sulfide composite according to any one of claims 3 to 5.

7. A potassium ion battery comprising the negative electrode for a potassium ion battery according to claim 6.

8. Use of a composite prepared by the method for preparing a biocarbon-molybdenum sulfide-tungsten sulfide composite according to claim 1 or 2 or a composite according to any one of claims 3 to 5 in preparing a negative electrode for a potassium ion battery.

Citation Information

Patent Citations

  • Transition metal chalcogenide composite material and preparation method and application thereof

    CN110690419A

  • Preparation method for WS2-in situ biological carbon composite anode material

    CN105047862A

  • Manufacturing methodof rhenium disulfide supercapacitor based on biological template method growth

    CN111170370A